2019
DOI: 10.1002/smj.3003
|View full text |Cite
|
Sign up to set email alerts
|

CEO's age and the performance of closely held firms

Abstract: Research Summary Using detailed ownership and financial information from a large sample of owner‐managed private firms in three Western European countries, this paper examines the relationship between CEO's age and firm's performance. Tracking firms over time, we find that as a CEO ages, the firm experiences lower investment, lower sales growth, and lower profitability, but also higher probability of survival, suggesting a trade‐off between the managerial approaches of younger and older CEOs. These results are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 114 publications
5
80
0
2
Order By: Relevance
“…One of them addresses the role of CEO characteristics. Specifically, researchers have examined the role of the form of appointment of the CEO (internal or external) (Karaevli & Zajac, 2013;Hoitash & Mkrtchyan, 2018), academic background (Mintzberg, 2004;Gottesman & Morey, 2010;Miller & Xu, 2019), age (Hambrick & Mason, 1984;Barker & Mueller, 2002;Belenzon et al, 2019), tenure in the firm (Hambrick & Fukutomi, 1991;Henderson, Miller, & Hambrick, 2006), or the country of origin (Crossland & Hambrick, 2011;Ioannou & Serafeim, 2012;Boone, Lokshin, Guenter, & Belderbos, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One of them addresses the role of CEO characteristics. Specifically, researchers have examined the role of the form of appointment of the CEO (internal or external) (Karaevli & Zajac, 2013;Hoitash & Mkrtchyan, 2018), academic background (Mintzberg, 2004;Gottesman & Morey, 2010;Miller & Xu, 2019), age (Hambrick & Mason, 1984;Barker & Mueller, 2002;Belenzon et al, 2019), tenure in the firm (Hambrick & Fukutomi, 1991;Henderson, Miller, & Hambrick, 2006), or the country of origin (Crossland & Hambrick, 2011;Ioannou & Serafeim, 2012;Boone, Lokshin, Guenter, & Belderbos, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors evidence that the age of the entrepreneur is unrelated to the growth of the firm (Cassar, 2006). Belenzon, Shamshur & Zarutskie (2019) found that as an entrepreneur ages the firm experiences lower sales growth. Finally, some studies verify that older entrepreneurs present, on average, better conditions and resources to make their business grow (Fadahunsi, 2012;Reeg, 2013).…”
Section: Agementioning
confidence: 99%
“…Bertrand and Schoar (2003) demonstrated that manager effects have significant explanatory power for the variance in firm's decision making. Researchers also explored the impacts of CEO demographics and psychological traits on firm decision making, including age (Belenzon, Shamshur, & Zarutskie, 2019; Hambrick, 2007; Hambrick & Fukutomi, 1991), gender (Anderson, 2003; Berger, Kick, & Schaeck, 2014; Datta & Guthrie, 1994; Huang, 2013; Manner, 2010), tenure (Hambrick & Fukutomi, 1991; Hirshleifer, 1993; Miller, 1991; Yudan, 2010), risk attitude, and overconfidence (Cain & McKeon, 2016; Graham et al, 2013; Huang, Tan, & Faff, 2016; Malmendier, Tate, & Yan, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%